2019
DOI: 10.3389/fphys.2019.00409
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Pre-season Training Load With In-Season Biochemical Markers, Injuries and Performance in Professional Soccer Players

Abstract: Introduction There is controversy in the literature in regards of the link between training load and injury rate. Thus, the aims of this non-interventional study were to evaluate relationships between pre-season training load with biochemical markers, injury incidence and performance during the first month of the competitive period in professional soccer players. Materials and Methods Healthy professional soccer players were enrolled in this study over two pre-season pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
2
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 50 publications
(76 reference statements)
0
44
2
9
Order By: Relevance
“…Our findings run counter to those in a single French professional soccer team where there was no association between preseason training and in-season injury rates, 6 but they extend previous studies in rugby, 25 American football, 21 and Australian football 5,22 where athletes who completed more preseason training were less likely to be hurt during the in-season period. Improved physical fitness and well-developed physical qualities protect players from the demands of the competitive soccer season.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Our findings run counter to those in a single French professional soccer team where there was no association between preseason training and in-season injury rates, 6 but they extend previous studies in rugby, 25 American football, 21 and Australian football 5,22 where athletes who completed more preseason training were less likely to be hurt during the in-season period. Improved physical fitness and well-developed physical qualities protect players from the demands of the competitive soccer season.…”
Section: Discussioncontrasting
confidence: 84%
“…Only 1 study has directly evaluated the relationship between preseason training and in-season injury risk in elite soccer. 6 There was no association between a single team’s (35 total players) preseason training workloads and in-season injury rates across 2 seasons. To our knowledge, no study has yet compared the preseason training workloads of multiple teams and their association with in-season injury rates.…”
mentioning
confidence: 90%
“…It has been recently revealed that training load during the pre-season (6 weeks) of a professional elite football team may not have an effect on team physical performance during the first five official matches of the season, since no relationship was found between training load and injury rate, inflammation and muscle damage markers (Coppalle et al, 2019 ). One of the most significant findings from an initial Football Association's epidemiological study was the disproportionately high number of training injuries during July, a month that corresponds to the preseason period (Woods et al, 2002 ).…”
mentioning
confidence: 99%
“…The sRPE, obtained after the completion of training and/or the match, classifies the general difficulty of the session by multiplying the RPE by the duration of the exercise, in minutes [ 111 ] and, based on the scale of 0 to 10, has been widely used in the evaluation of internal load, both in training and in competition [ 7 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 24 , 26 , 28 , 29 , 30 , 31 , 32 , 39 , 61 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 74 , 75 , 77 , 78 , 79 , 80 , 81 , 84 , 85 ]. On the other hand, Coppalle [ 66 ] and Owen [ 86 ] used the 6–20 scale to determine sRPE. The application of this inventory has often occurred shortly after the end of the training session and/or match (15 to 30 min); however, it was applied by Owen [ 86 ] in the morning after training, in order to ensure that the perceived exertion reflected the whole session and not the last effort.…”
Section: Internal Load Measuresmentioning
confidence: 99%